Analysis of Social and Environmental Impact Measurement Difficulties in Green Investment and Sustainable Finance - Djafar, Djafar; Tabsir, Muhammad Kusnady; Rachmawaty, Rachmawaty; Djabir, Muh; Pratiwi Ar, Dhita (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the challenges in measuring social and environmental impacts in green investment and sustainable finance, with a focus on methodological inconsistencies, data quality, and the application of sustainability standards. It also explores the gap between theoretical frameworks and their practical implementation in corporate sustainability reporting. Research Method: The research employed a systematic literature review (SLR) approach to synthesize existing studies and identify recurring challenges in impact assessment methodologies. The SLR integrated theoretical perspectives, such as stakeholder and legitimacy theories, to connect the findings to established frameworks, highlighting their practical limitations in real-world applications. Results and Discussion: The study revealed significant inconsistencies in the methodologies used for impact measurement, including the limitations of both quantitative and qualitative approaches. Issues with data quality, such as reliance on self-reported data without adequate third-party verification, compromised the reliability of sustainability claims. Additionally, varying and ambiguous sustainability standards were shown to create confusion and potential greenwashing. The findings highlight the disparity between theoretical frameworks and their practical application, which undermines stakeholder trust and organizational legitimacy. Implications: This research contributes to academic knowledge by providing an integrated view of current challenges in sustainability impact measurement. It recommends adopting mixed-methods approaches and advanced technologies, such as blockchain, to improve transparency and reliability in sustainability reporting. The study suggests that aligning methodologies with comprehensive theoretical frameworks can enhance corporate practices and bolster stakeholder confidence in sustainability claims.